Heparin sensing based on multisite-binding induced highly ordered perylene nanoaggregates. Issue 87 (12th October 2020) - Aryal, Gyan H.; Rana, Ganesh R.; Guo, Fei; Hunter, Kenneth W.; Huang, Liming
Abstract : Heparin sensing based on highly ordered perylene nanoaggregates with ultra-low fluorescence and the use of host–guest complexes to improve the sensitivity. Abstract : Highly ordered perylene nanoaggregates with ultra-low fluorescence were employed for the selective and sensitive fluorescence sensing of heparin. A supramolecular host–guest complex was used as a displacement probe to improve the sensitivity.